Does femoroacetabular impingement syndrome affect range of motion? A systematic review with meta-analysis. Issue 12023 (11th November 2022) - Albertoni, Davide Bruno; Gianola, Silvia; Bargeri, Silvia; Hoxhaj, Ilda; Munari, Alice; Maffulli, Nicola; Castellini, Greta
Abstract: Background: It is unclear whether femoroacetabular impingement syndrome (FAIS) affect hip range of motion (ROM). Sources of data: We performed a systematic review with meta-analysis searching six electronic databases from inception to March 21, 2022. We included studies assessing hip ROM in FAIS, FAI morphology without symptoms (FAIm), and healthy controls. Mean differences between groups were measured in ROM degrees with 95% confidence interval (CI). Areas of agreement: A total of 17 studies (1702 hips) were included. Comparison of FAIS patients versus healthy controls showed that hip ROM was clinically and statistically reduced in FAIS for internal rotation (90° hip flexion, −8.01°, 95% CI: –11.21, −4.90; 0° hip flexion −6.38°, 95% CI: –9.79, −2.97); adduction (90° hip flexion, −4.74°, 95% CI: –8.13, −1.34); flexion (−5.41°, 95% CI: –7.05, −3.49), abduction (0° hip flexion, −5.76°, 95% CI: –8.38, −3.23), and external rotation (90° hip flexion, −3.5°, 95% CI: –5.32, −1.67) ranging from low to high certainty of evidence. Comparison of FAIm versus healthy controls showed no statistically significant differences in any direction of movement, albeit with uncertainty of evidence. Areas of controversy: The certainty of evidence was unclear, particularly for asymptomatic FAIm. Growing points: Hip ROM may be reduced in all directions except extension in FAIS compared to controls. Hip ROM may not be restricted in asymptomatic FAIm. Areas timely for developing research: Further studies are needed to resolve the uncertainty of evidence about ROM restrictions in asymptomatic FAIm compared to healthy controls.